Pemberdayaan Ibu-Ibu Rumah Tangga Desa Loa Janan Ulu Dalam Pemanfaatan Limbah Rumah Tangga Metode Takakura Menjadi Pupuk Organik Untuk Mendukung Rumah Pangan Lestari (RPL) - Mirasari, Rossy; Rahman, Arief; Anwar, Rusli; Marlendi, Sri (Jurnal Pengabdian Kampus, 2023)
In this era of globalization, environmental problems have become global issues. Society are aware of the dangers posed by environmental damage. One of the causes of environmental damage is environmental pollution caused by the accumulation of waste produced by humans. Loa Janan Ulu, Kutai Kartanegara regency is the village with the highest density with 1,007.90 population/km2. There are 3,401 households in the village area ladder. Housewives are also part of society produce waste or rubbish every day. Every day kitchen activities are included contributes quite a significant amount of waste. Kitchen waste that has been around all this time just thrown straight into landfill or burned straight away. Manage of kitchen waste needs to be dealt with so that it can be utilized as an ingredient for organic fertilizer. Composting is one of the efforts to process waste in order to recycle it organic waste with the concept of decomposing organic materials through processes weathering, besides being non-damaging and environmentally friendly. The simple way to make compost is the takakura basket method with help Local Organism Molecules. The solutions offered are: 1. Giving information about processing kitchen waste using the zero waste concept; 2. Giving information on the benefits of using organic fertilizer for partners and the environment with socialization; 3. Providing training on processing organic waste using methods Takakura makes simple use of surrounding resources. this activity planned for 4 months and carried out in Loa Janan Ulu Village, District Loa Janan, Kutai Kartanegara Regency. The result of the dedication of Loa Village Women Janan Ulu felt benefits such as increasing knowledge and insight handling organic household waste so that it becomes added value for plants in the yard includes vegetable plants that are consumed every day as well as ornamental plants. The follow-up to this activity requires training grow crops in the yard properly to utilize the land area available yard.